Isothermal Phase Transformations in a Low Carbon Steel During Single and Two-Step Partitioning - Castro-Cerda, F; Hernandez-Duran, E (Springer, 2020)
Single and two-step heat treatments were performed on hot-rolled 0.2C-2Mn-1.4Si-0.3Mo steel. The microstructure was characterized by means of optical and scanning electron microscopy and X-ray diffraction measurements. The results showed that the main microstructural components are tempered martensite, bainite, and retained austenite. The thermodynamic analysis showed that the constrained carbon equilibrium in the presence of cementite CCEθ model fits the experimental data for the isothermal heat treatment at a temperature well below the MS. Neither of the existing models for predicting the equilibrium between martensite and austenite (i.e., constrained carbon equilibrium CCE and CCEθ) seems to predict the measured austenitic carbon content nearby the MS, which might indicate that local equilibrium (LE) conditions during bainitic transformation govern the final stage of both single and two-phase heat treatments. © 2020, The Minerals, Metals & Materials Society and ASM International.